Pemurnian Parsial dan Karakterisasi Amilase dari Bakteri Laut Arthrobacter arilaitensis LBF-003 - Rahmasari, Dianti; Wijanarka, Wijanarka; Pujiyanto, Sri; Rahmani, Nanik; Yopi, Yopi (JURNAL BIOLOGI INDONESIA, 2016)
Starch is an abundant carbon source in nature, and ?-amylase (1, 4-?-D-glucanohydrolase; EC 3.2.1.1), which hydrolyzes ?-1, 4-glucosidic linkage in starch-related molecules. Microbe ?-amylase production is a hydrolytic enzyme and one ofinterest in its microbial production has increased dramatically due to its wide spread use in food, textile, baking anddetergent industries in recent years. Here we report ?-amylase from marine bacterium which was purified andcharacterized, as well as analyzed its hydrolysis product on starch. The enzyme of Arthrobacter arilaitensis partiallypurified by acetone precipitation with 90% and ion exchange chromatography produced specific activity 0.25 U/mg and0.38 U/mg, and itâs purity rate increased until 1.14 fold compared with former crude extract. Purifed extracelluler amilasehad an optimum activity at temperature 50Â°C and pH 9.0. An apparent molecular mass was between 50-75 kDa, asestimated by zimogram electrophoresis. Hydrolysis products of this enzyme on starch were maltose, maltotriose andmaltoheptaose.Keywords: alfa amylase, marine bacterium, Arthrobacter arilaitensis, purification, charaterization